PREVALENCE AND DEMOGRAPHIC CORRELATES OF DEPRESSION, ANXIETY, AND STRESS AMONG UNIVERSITY STUDENTS - Shafiq, Sameera; Fatima, Zainab; Bano, Zakia (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To study the prevalence and demographic correlates of depression, anxiety and stress among university students.Study Design: Correlational Research DesignPlace and Duration of Study: Data was collected from University of Gujrat, Gujrat between 6 February, 2019 to, 5 April 2019.Material and Methods: A sample of 400 students selected by random sampling technique were approached from two departments namely Psychology and Environmental Sciences which were randomly selected from Faculty of Social Sciences and Faculty of Sciences respectively. Depression, Anxiety, Stress Scale-42 (DASS-42) along with demographic sheet and informed consent forms were administered.Results: Prevalence of moderate to extremely severe level of depression, anxiety, and stress as 54.8%, 73.5%, and 44.3% respectively was found among university students.  Depression, anxiety, and stress were found to be positively and significantly related, having high Cronbach’s Alpha Reliability coefficients. Among demographic variables, type of study group significantly predicted level of depression, anxiety, and stress among students. Age and income significantly predicted level of depression, while the former also contributed in anxiety. However, gender was significant predictor of stress only among university students.Conclusion: The prevalence of depression, anxiety and stress was high among university students in Gujrat. There is a need for launching of counseling and preventive interventions to halt psychiatric disorders at early stages among university students.